A Silicon Integrated Microwave Vector Network Analyzer for Biomedical Sensor Read-Out Applications - Nehring, Johannes; Nasr, Ismail; Borutta, Karl; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium (IMS), 2014)
This paper proposes an integrated reflectometer for biomedical sensor read-out applications using a low-cost silicon- germanium technology. The heterodyne reflectometer consists of two integrated cross-coupled oscillators, a set of two directional couplers as well as Gilbert-Cell downconversion mixers. A dual phase-locked-loop architecture guarantees the phase lock of both on-chip signal sources to an external reference oscillator. An OSM-calibration was applied to the reflectometer and measure- ments of the complex reflection coefficient of an arbitrary device under test (DUT) showed excellent agreement with the results of a commercial vector network analyzer. As a proof of concept for sensor read-out, five solutions with different mixture ratios were characterized with a dielectric probe connected to the reflectometer.
elib2cris::1512001600,nehring2014